Chinese Nurses' Ethical Concerns in a Neurological Ward - Tang, Ping Fen (Nursing ethics, 2007)
Our aim was to describe Chinese nurses' experiences of workplace distress and ethical dilemmas on a neurological ward. Qualitative interviews were performed with 20 nurses. On using latent content analysis, themes emerged in four content areas: ethical dilemmas, workplace distress, quality of nursing and managing distress. The ethical dilemmas were: (1) conflicting views on optimal treatment and nursing; (2) treatment choice meeting with financial constraints; and (3) misalignment of nursing responsibilities, competence and available resources. The patients' relatives lacked respect for the nurses' skills. Other dilemmas could be traced to the transition from a planned to a market economy, resulting in an excessive workload and treatment withdrawal for financial reasons. Lack of resources was perceived as an obstacle to proper patient care in addition to hospital organization, decreasing the quality of nursing, and increasing moral and workplace distress. The nurses managed mainly by striving for competence, which gave them hope for the future.